(untitled) (Quinto Sol, 2022)
This work analyzes the performance and confluence of public actors in the process of extension of soy cultivation in the southeast of Buenos Aires since the early 1970s. A qualitative methodology was used with the crossing of quantitative data. In this way, an analysis of the area planted with soybeans and other crops in the area was carried out, to then evaluate the actions of Balcarce Agricultural Station belonging to National Institute of Agricultural Technology. This is how the research process on this topic was characterized and its dissemination to the surrounding rural area, considering in turn the link with private actors.